Positive pole piece, battery and electric device

By layering the positive electrode active material in the positive electrode sheet and adding solid lubricant, the problems of low battery energy density and poor capacity retention after circulation are solved, and a higher cycle capacity retention and energy density are achieved.

CN119447167APending Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310952238.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The battery using a cathode sheet containing a cathode active material with different electron conductivity has a problem that the energy density is low and the capacity retention rate after circulation is low.

Method used

A positive electrode sheet arranged in a layered manner includes a first positive electrode active material layer and a second positive electrode active material layer on the current collector. A solid lubricant is added to the first positive electrode active material layer to reduce the electron conductivity and reduce the activity of the two positive electrodes. The electronic conductivity difference of the material layer reduces phase transition and friction impedance.

Benefits of technology

It improves the battery's cycle capacity retention rate and energy density, extends the cycle life, and reduces the internal stress during the production of the positive electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447167A_ABST
    Figure CN119447167A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a battery and a power utilization device, and relates to the field of batteries. The positive pole piece comprises a current collector, and a first positive active material layer and a second positive active material layer which are arranged on the current collector, the first positive active material layer comprises a first positive active material and a solid lubricant, the electronic conductivity of the first positive active material is a1, the second positive active material layer comprises a second positive active material, and the electronic conductivity of the solid lubricant is a2. The electronic conductivity of the second positive electrode active material is a2, and a1 is greater than a2; the electronic conductivity of the solid lubricant is smaller than a1 and smaller than or equal to 10 <-2 > S / cm, and the solid lubricant can improve the capacity retention ratio and the energy density of the battery after circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a positive electrode sheet, a battery and an electrical device. Background Art

[0002] As the market demands for high energy density, excellent cycle life, and higher safety performance of batteries, a combination of multiple positive electrode active materials is usually used to improve the overall performance of the battery. However, in actual use, batteries using positive electrode plates containing positive electrode active materials with different electronic conductivities have low energy density and low capacity retention after cycling. Summary of the invention

[0003] In view of the above problems, the present application proposes a positive electrode plate, a battery and an electrical device, which can improve the technical problems of low energy density and low capacity retention rate after cycling of batteries using positive electrode plates containing positive electrode active materials with different electronic conductivities.

[0004] In a first aspect, an embodiment of the present application provides a positive electrode sheet, which includes a current collector, and a first positive electrode active material layer and a second positive electrode active material layer disposed on the current collector, wherein the first positive electrode active material layer includes a first positive electrode active material and a solid lubricant, the electronic conductivity of the first positive electrode active material is a1, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is a2, a1 is greater than a2; the electronic conductivity of the solid lubricant is less than a1 and less than or equal to 10 -2 S / cm.

[0005] In the technical solution of the embodiment of the present application, a layered arrangement is adopted to make the phase change mainly concentrated at the interface of the two positive electrode active material layers to reduce the phase change, which is beneficial to improve the cycle capacity retention rate of the battery containing the positive electrode plate. Since the electronic conductivity of the first positive electrode active material is greater than the electronic conductivity of the second positive electrode active material, the electronic conductivity of the first positive electrode active material is less than or equal to 10. -2 The specific solid lubricant with a RPMI of 100 S / cm can, on the one hand, reduce the electronic conductivity of the first positive electrode active material layer to narrow the difference in electronic conductivity between the two positive electrode active material layers, reduce the phase change at the interface of the two positive electrode active material layers, and enable the battery to have a higher cycle capacity retention rate during the cycle process; on the other hand, the solid lubricant can reduce the friction impedance between the particles of the first positive electrode active material, reduce the internal stress of the first positive electrode active material during cold pressing during the production of the positive electrode plate, and increase the compaction density of the first positive electrode active material layer to increase the compaction density of the positive electrode plate as a whole, thereby improving the battery energy density.

[0006] In some embodiments, the solid lubricant has a particulate morphology or a lamellar morphology.

[0007] Optionally, the particle morphology includes a spherical or spheroidal shape.

[0008] The solid lubricant with the above-mentioned morphological characteristics has good lubrication effect, which is beneficial to effectively reduce the friction impedance between the particles of the first positive electrode active material, increase the compaction density of the first positive electrode active material layer to increase the compaction density of the positive electrode sheet as a whole, and improve the battery energy density.

[0009] In some embodiments, the solid lubricant has a volume particle size distribution Dv50 that is less than or equal to 0.3 times the volume particle size distribution Dv50 of the first positive electrode active material.

[0010] Optionally, the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.3 times, optionally 0.05-0.2 times, the volume particle size distribution Dv50 of the first positive electrode active material.

[0011] The battery has good cycle capacity retention and energy density within the above range.

[0012] In some embodiments, the volume particle size distribution Dv50 of the first positive electrode active material is 0.4-30 um. In this particle size range, a suitable solid lubricant can be added to reduce the phase change at the interface of the two positive electrode active material layers, effectively improving the cycle capacity retention rate of the battery.

[0013] In some embodiments, the mass proportion of the solid lubricant in the first positive electrode active material layer is less than or equal to 6%, optionally 0.1%-6%, and further optionally 0.4%-6%. By controlling the mass proportion of the solid lubricant within the above range, the battery can improve the cycle capacity retention rate of the battery while having a better battery energy density.

[0014] In some embodiments, the solid lubricant includes at least one of an inorganic lubricant and an organic lubricant;

[0015] Optionally, the organic lubricant includes thermosetting resin particles, and the thermosetting resin includes at least one of phenolic resin, urea-formaldehyde resin, melamine-formaldehyde resin, epoxy resin, polyurethane resin, and polyimide resin;

[0016] Optionally, the inorganic lubricant includes at least one of a layered van der Waals material, an inorganic particle having a dielectric constant of 5 or more, and an inorganic particle having ion conductivity but not storing ions;

[0017] Optionally, the layered van der Waals material comprises molybdenum disulfide.

[0018] Optionally, inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1- n Ti n O3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.

[0019] Optionally, inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following, 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7.

[0020] The above-mentioned inorganic lubricant and organic lubricant can reduce the friction impedance between the particles of the first positive electrode active material, and can also reduce the phase change at the interface of the two positive electrode active material layers, effectively improving the cycle capacity retention rate of the battery and increasing the cycle life.

[0021] In some embodiments, the electronic conductivity of the solid lubricant is 10 -15 -10 -2 The electronic conductivity of the solid lubricant within this range is low, which is beneficial to reducing the electronic conductivity of the first positive electrode active material layer, reducing the phase change caused by the difference in electronic conductivity at the interface of the two positive electrode active material layers, and is beneficial to improving the cycle capacity retention rate of the battery.

[0022] In some embodiments, 1<a1:a2≤10. The ratio of the electronic conductivity of the second positive electrode active material to the electronic conductivity of the first positive electrode active material is controlled within a reasonable range, so that after adding the solid lubricant, the electronic conductivity of the first positive electrode active material layer can be reduced to reduce the difference in electronic conductivity between the two positive electrode active material layers, reduce the phase change at the interface of the two positive electrode active material layers, and enable the battery to have a higher cycle capacity retention rate during the cycle process.

[0023] In some embodiments, a1 is 10-10 -9 S / cm; and / or, a2 is 10 -1 -10 -10 Controlling the electronic conductivity of the second positive electrode active material and the electronic conductivity of the first positive electrode active material within the above range is beneficial for adding the solid lubricant and coordinating with the solid lubricant, so that the battery has a higher cycle capacity retention rate during the cycle process.

[0024] In some embodiments, the first positive electrode active material includes an olivine structure phosphate material, and the second positive electrode active material includes a layered transition metal oxide. By rationally combining the olivine structure phosphate material and the layered transition metal oxide, the battery has both safety and high energy density while having a better cycle retention rate.

[0025] In some embodiments, the olivine structure phosphate material includes Li a Fe b M 1-b P 1-m O 4-n , wherein M includes at least one of other metal elements except Fe, wherein 0<a≤1.1, 0.3≤b≤1, 0≤m≤0.1, 0≤n≤0.1.

[0026] Optionally, M includes at least one of Mn, Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge.

[0027] Optionally, the olivine structure phosphate material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0028] In some embodiments, the layered transition metal oxide includes LiCoO2, LiMnO2, LiNiO2, Li a Ni x Co y M1 1-x-y O 2+d , z Li2MnO3 (1-z) At least one of LiM2O2, wherein M1 includes at least one of Mn, Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, and M2 includes at least one of Co, Ni, and Mn, 0.5≤x≤1.0, 0≤y<0.5, x+y<1, 0.2≤a<1.2, -0.02≤d<0.02, and 0<z<1.

[0029] Optionally, the layered transition metal oxide includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium-rich material, nickel-cobalt-manganese ternary material and manganese-cobalt-aluminum ternary material.

[0030] In some embodiments, the first positive electrode active material layer is located on a side of the second positive electrode active material layer close to the current collector. The above arrangement can enable the battery to have a better capacity retention rate.

[0031] In a second aspect, the present application provides a battery, which includes the positive electrode plate in the above embodiment.

[0032] In a third aspect, the present application provides an electrical device, which includes the battery in the above embodiment, and the battery is used to provide electrical energy.

[0033] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0035] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;

[0036] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;

[0037] Figure 3A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;

[0038] Figure 4 This is a schematic diagram of the structure of the positive electrode sheet of some embodiments of the present application;

[0039] Figure 5 This is a schematic diagram of the structure of the positive electrode sheet of some embodiments of the present application;

[0040] Figure 6 This is a SEM image of the phase change at the interlayer interface of the positive electrode sheet after 200 cycles of Example 1 of the present application;

[0041] Figure 7 This is a SEM image of the phase change at the interlayer interface of the positive electrode sheet of comparative example 2 of the present application after 200 cycles.

[0042] The reference numerals in the specific implementation manner are as follows:

[0043] 1000-Vehicles;

[0044] 100-battery; 200-controller; 300-motor;

[0045] 10-box; 11-first part; 12-second part;

[0046] 20-battery cell; 21-end cover; 21a-electrode terminal; 22-housing; 23-electrode assembly; 23a-electrode ear;

[0047] 30 - positive electrode sheet; 31 - current collector; 32 - first positive electrode active material layer; 33 - second positive electrode active material layer. DETAILED DESCRIPTION

[0048] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0050] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0051] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0052] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0053] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0054] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0055] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0056] At present, from the perspective of market development, the application of batteries is becoming more and more extensive. Batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of battery application areas, its market demand is also constantly expanding.

[0057] Based on the market's requirements for high energy density, excellent cycle life, and high safety performance of batteries, a combination of multiple positive electrode active materials is usually used in the hope of improving the overall performance of the battery. However, in actual use, batteries using positive electrode plates containing positive electrode active materials with different electronic conductivities have low energy density and low capacity retention after cycling.

[0058] In order to improve the above technical problems, the present application adopts a method of stacking a first positive electrode active material layer and a second positive electrode active material layer on a current collector; the first positive electrode active material layer includes a first positive electrode active material and a solid lubricant, the electronic conductivity of the first positive electrode active material is a1, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is a2, a1 is greater than a2; the electronic conductivity of the solid lubricant is less than a1 and less than or equal to 10 -2 S / cm.

[0059] In the technical solution of the embodiment of the present application:

[0060] Firstly, by adopting a layered arrangement, the phase change is mainly concentrated at the interface between the two positive electrode active material layers to reduce the phase change, which is beneficial to improving the cycle capacity retention rate of the battery containing the positive electrode plate.

[0061] Secondly, since the electronic conductivity of the first positive electrode active material is greater than that of the second positive electrode active material, a conductive material having an electronic conductivity less than a1 and less than or equal to 10 is added to the first positive electrode active material layer. -2 The specific solid lubricant with a RPMI of 100 S / cm can, on the one hand, reduce the electronic conductivity of the first positive electrode active material layer to narrow the difference in electronic conductivity between the two positive electrode active material layers, reduce the phase change at the interface of the two positive electrode active material layers, and enable the battery to have a higher cycle capacity retention rate during the cycle process; on the other hand, the solid lubricant can reduce the friction impedance between the particles of the first positive electrode active material, reduce the internal stress of the first positive electrode active material during cold pressing during the production of the positive electrode plate, and increase the compaction density of the first positive electrode active material layer to increase the compaction density of the positive electrode plate as a whole, thereby improving the battery energy density.

[0062] The battery disclosed in the embodiment of the present application can be used, but not limited to, in electric devices such as vehicles, ships or aircraft. A power supply system comprising the battery disclosed in the present application can be used to form the electric device, which is conducive to improving the energy density and capacity retention rate after cycling of the battery using the positive electrode sheet containing the positive electrode active material layer with different electronic conductivity.

[0063] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, a spacecraft, etc.

[0064] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.

[0065] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0066] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0067] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may also include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0068] Please refer to Figure 2 , Figure 2An exploded view of a battery 100 provided in some embodiments of the present application. The battery 100 includes a box 10 and a battery cell 20, and the battery cell 20 is contained in the box 10. Among them, the box 10 is used to provide a storage space for the battery cell 20, and the box 10 can adopt a variety of structures. In some embodiments, the box 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, the first part 11 may be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box 10 formed by the first part 11 and the second part 12 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0069] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.

[0070] Each battery cell 20 may be a secondary battery or a primary battery. The battery cell 20 may be cylindrical, flat, rectangular or in other shapes.

[0071] Please refer to Figure 3 , Figure 3 The schematic diagram of the exploded structure of the battery cell 20 provided in some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.

[0072] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0073] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0074] The electrode assembly 23 is a component in the battery cell 20 where electrochemical reactions occur. One or more electrode assemblies 23 may be included in the housing 22. The electrode assembly 23 is mainly formed by winding or stacking positive and negative electrode sheets, and a separator is usually provided between the positive and negative electrode sheets. The parts of the positive and negative electrode sheets with active materials constitute the main body of the electrode assembly, and the parts of the positive and negative electrode sheets without active materials each constitute a tab 23a. The positive tab and the negative tab may be located together at one end of the main body or at both ends of the main body, respectively. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 23a connects the electrode terminals to form a current loop.

[0075] See also Figure 3 as well as Figure 4 According to some embodiments of the present application, the positive electrode sheet 30 includes a current collector 31, and a first positive electrode active material layer 32 and a second positive electrode active material layer 33 disposed on the current collector 31, the first positive electrode active material layer 32 includes a first positive electrode active material and a solid lubricant, the electronic conductivity of the first positive electrode active material is a1, the second positive electrode active material layer 33 includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is a2, a1 is greater than a2, and the electronic conductivity of the solid lubricant is less than a1 and less than or equal to 10 -2 S / cm.

[0076] The current collector 31 may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil or an aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0077] The positive electrode active material layer refers to the film layer containing the positive electrode active material for reacting with the electrolyte during the charge and discharge process of the battery. In addition to the positive electrode active material, the positive electrode active material layer may also generally contain a binder and a conductive agent. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0078] Since the electronic conductivity of the solid lubricant is less than a1 and less than or equal to 10 -2 S / cm, so introducing it into the first positive electrode active material layer 32 can reduce the electronic conductivity of the first positive electrode active material layer 32, thereby narrowing the difference in electronic conductivity between the two positive electrode active material layers, reducing the phase change at the interface of the two positive electrode active material layers, and making the battery have a higher cycle capacity retention rate during the cycle process.

[0079] In the technical solution of the embodiment of the present application, a layered arrangement is adopted to make the phase change mainly concentrated at the interface of the two layers of positive electrode active material layers to reduce the phase change, which is beneficial to improve the cycle capacity retention rate of the battery containing the positive electrode plate 30. Since the electronic conductivity of the first positive electrode active material is greater than the electronic conductivity of the second positive electrode active material, a positive electrode having an electronic conductivity less than a1 and less than or equal to 10 is added to the first positive electrode active material layer 32. -2 The specific solid lubricant with a S / cm can, on the one hand, reduce the friction impedance between the particles of the first positive electrode active material, reduce the internal stress of the first positive electrode active material during cold pressing during the production of the positive electrode plate 30, and increase the compaction density of the first positive electrode active material layer 32 to increase the compaction density of the positive electrode plate 30 as a whole, thereby improving the battery energy density. On the other hand, it can reduce the electronic conductivity of the first positive electrode active material layer 32 to narrow the difference in electronic conductivity between the two layers of positive electrode active material layers, reduce the phase change at the interface of the two layers of positive electrode active material layers, and enable the battery to have a higher cycle capacity retention rate during the cycle process.

[0080] The current collector 31 has two opposite surfaces. In some embodiments, a first positive electrode active material layer 32 and a second positive electrode active material layer 33 are sequentially disposed on one surface of the current collector 31 .

[0081] like Figure 4 as well as Figure 5 As shown, in some other embodiments, the first positive electrode active material layer 32 and the second positive electrode active material layer 33 are sequentially disposed on both surfaces of the current collector 31 .

[0082] Optionally, the thickness of the first positive electrode active material layer 32 is 40-200 μm, and the thickness of the second positive electrode active material layer 33 is 40-200 μm.

[0083] The preparation method of the positive electrode plate 30 includes: obtaining a first slurry for preparing a first positive electrode active material layer 32 and a second slurry for preparing a second positive electrode active material layer 33, and according to the positions of the first positive electrode active material layer 32 and the second positive electrode active material layer 33 in the upper and lower directions, the first slurry and the second slurry are set in defined positions as the upper and lower layers, and then the two layers of slurry are coated on the collector 31 in a synchronous or step-by-step manner, and then dried and cold pressed to obtain the positive electrode plate 30.

[0084] According to some embodiments of the present application, the solid lubricant has a particle morphology or a layered morphology.

[0085] The particle morphology refers to the granular shape of the solid lubricant, which can transform the sliding friction between the first positive electrode active material during the cold pressing process into rolling friction, thereby reducing the friction impedance between the particles of the first positive electrode active material, reducing the internal stress of the first positive electrode active material during cold pressing during the production of the positive electrode plate 30, increasing the overall compaction density of the positive electrode plate 30, and increasing the battery energy density.

[0086] The layered morphology refers to a solid in which atoms or polyhedrons within the layer are interconnected by covalent bonds or ionic bonds, and the layers are connected by van der Waals forces. Since the layers are connected by van der Waals forces, the solid lubricant with a layered morphology can be peeled off into a structure with a few layers or even a single layer under the action of external force. Therefore, during the cold pressing process, it can be peeled off into a structure with a few layers or even a single layer under the action of external force, thereby producing a lubricating effect, reducing the friction impedance between the particles of the first positive electrode active material, increasing the overall compaction density of the positive electrode plate 30, and increasing the battery energy density.

[0087] Optionally, the particle morphology includes spherical or quasi-spherical shapes, which have good lubrication effects.

[0088] According to some embodiments of the present application, a volume particle size distribution Dv50 of the solid lubricant is less than or equal to 0.3 times a volume particle size distribution Dv50 of the first positive electrode active material.

[0089] The volume particle size distribution Dv50 refers to a particle size distribution parameter determined by a particle size distribution measurement value. For example, the volume particle size distribution Dv50 is determined by a particle size analyzer-laser diffraction method. Specifically, reference may be made to the standard GB / T 19077-2016, and measurement may be performed using a laser diffraction scattering particle size analyzer.

[0090] Within the above range, it is beneficial to improve the cycle capacity retention rate and energy density of the battery.

[0091] Optionally, the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.3 times the volume particle size distribution Dv50 of the first positive electrode active material.

[0092] The battery has good cycle capacity retention and energy density within the above range.

[0093] Illustratively, the volume particle size distribution Dv50 of the solid lubricant is any value among 0.05 times, 0.10 times, 0.11 times, 0.13 times, 0.15 times, 0.17 times, 0.20 times, 0.25 times, 0.3 times the volume particle size distribution Dv50 of the first positive electrode active material, or between any two values.

[0094] Optionally, the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.2 times the volume particle size distribution Dv50 of the first positive electrode active material.

[0095] According to some embodiments of the present application, the volume particle size distribution Dv50 of the first positive electrode active material is 0.4-30 um.

[0096] Incorporating a suitable solid lubricant within this particle size range can reduce the phase change at the interface between the two layers of positive electrode active material and effectively improve the cycle capacity retention rate of the battery.

[0097] Illustratively, the volume particle size distribution Dv50 of the first positive electrode active material is any value of 0.4 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or between any two values.

[0098] The volume particle size distribution Dv50 of the second positive electrode active material can be selected according to actual needs. For example, the volume particle size distribution Dv50 of the second positive electrode active material is 0.4-30 um.

[0099] According to some embodiments of the present application, the mass proportion of the solid lubricant in the first positive electrode active material layer is 0.05%-5%.

[0100] By controlling the mass proportion of the solid lubricant within the above range, the battery's cycle capacity retention rate can be improved while having a better battery energy density.

[0101] Optionally, the mass proportion of the solid lubricant in the first positive electrode active material layer is any value of 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, or between any two values.

[0102] Optionally, the solid lubricant accounts for 0.1% to 1% by mass in the first positive electrode active material layer.

[0103] According to some embodiments of the present application, the solid lubricant includes at least one of an inorganic lubricant and an organic lubricant.

[0104] Optionally, the organic lubricant includes thermosetting resin particles, and the thermosetting resin includes at least one of phenolic resin, urea-formaldehyde resin, melamine-formaldehyde resin, epoxy resin, polyurethane resin, and polyimide resin.

[0105] Optionally, the inorganic lubricant includes at least one of a layered van der Waals material, an inorganic particle having a dielectric constant of 5 or more, and an inorganic particle having ion conductivity but not storing ions.

[0106] Layered van der Waals solid materials are solids formed by stacking single atomic layers or polyhedral layers, in which atoms or polyhedrons within the layers are connected to each other by covalent bonds or ionic bonds, and the layers are connected by van der Waals forces.

[0107] Optionally, the layered van der Waals material comprises molybdenum disulfide.

[0108] Optionally, inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1- n Ti n O3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.

[0109] Optionally, inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4At least one of the following, 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7.

[0110] The above-mentioned inorganic lubricant and organic lubricant can reduce the friction impedance between the particles of the first positive electrode active material, and can also reduce the phase change at the interface of the two positive electrode active material layers, effectively improving the cycle capacity retention rate of the battery and increasing the cycle life.

[0111] According to some embodiments of the present application, the electronic conductivity of the solid lubricant is 10 -15 -10 -2 S / cm.

[0112] Within this range, the electronic conductivity of the first positive electrode active material layer can be effectively reduced, and the phase change caused by the difference in electronic conductivity at the interface between the two positive electrode active material layers can be reduced, which is beneficial to improving the cycle capacity retention rate of the battery.

[0113] According to some embodiments of the present application, 1<a1:a2≤10.

[0114] The ratio of the electronic conductivity of the second positive electrode active material to the electronic conductivity of the first positive electrode active material is controlled within a reasonable range, so that after adding the solid lubricant, the electronic conductivity of the first positive electrode active material layer can be reduced to narrow the conductivity difference between the two positive electrode active material layers, reduce the phase change at the interface of the two positive electrode active material layers, and enable the battery to have a higher cycle capacity retention rate during the cycle process.

[0115] According to some embodiments of the present application, a1 is 10-10 -9 S / cm; and / or, a2 is 10 -1 -10 -10 S / cm.

[0116] Controlling the electronic conductivity of the second positive electrode active material and the electronic conductivity of the first positive electrode active material within the above range is beneficial for adding and coordinating with the solid lubricant, so that the battery has a higher cycle capacity retention rate during the cycle process.

[0117] According to some embodiments of the present application, the first positive electrode active material includes an olivine structure phosphate material, and the second positive electrode active material includes a layered transition metal oxide.

[0118] By rationally combining olivine structure phosphate materials and layered transition metal oxides, the battery can have both safety and high energy density while having a good cycle retention rate. By adding solid lubricants to the first positive electrode active material layer, the electronic conductivity of the first positive electrode active material layer can be reduced, and the over-discharge of the layered transition metal oxide and excessive release of lithium ions can be avoided, which will cause the collapse of the ternary structure and lead to obvious battery attenuation. The difference in electronic conductivity between the two layers of positive electrode active material layers can be reduced, and the phase change at the interface between the two layers can be reduced, thereby improving the cycle capacity retention rate of the battery using the positive electrode sheet.

[0119] Optionally, the surface of the olivine structure phosphate material has a carbon coating layer, and the carbon content of the carbon coating layer is 0.1-3%. Within the above range, the electronic conductivity of the olivine structure phosphate material can be effectively improved, so that the electronic conductivity of the first positive electrode active material is greater than that of the second positive electrode active material, and the specific capacity of the first positive electrode active material is high, which is conducive to improving the energy density of the battery.

[0120] According to some embodiments of the present application, the olivine structure phosphate material includes Li a Fe b M 1-b P 1-m O 4-n , wherein M includes at least one of other metal elements except Fe, wherein 0<a≤1.1, 0.3≤b≤1, 0≤m≤0.1, 0≤n≤0.1.

[0121] Optionally, M includes at least one of Mn, Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge.

[0122] Exemplarily, olivine structure phosphate materials include but are not limited to LiFePO4, LiMn 0.1 Fe 0.9 PO4、LiMn 0.2 Fe 0.8 PO4、LiMn 0.3 Fe 0.7 PO4、LiMn 0.4 Fe 0.6 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.7 Fe 0.3 PO4、LiMn 0.8 Fe 0.2 PO4、LiMn 0.9 Fe 0.1 PO4, LiMnPO4, etc.

[0123] Optionally, the olivine structure phosphate material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0124] According to some embodiments of the present application, the layered transition metal oxide includes LiCoO2, LiMnO2, LiNiO2, Li a Ni x Co y M1 1-x-y O 2+d , z Li2MnO3 (1-z) At least one of LiM2O2, wherein M1 includes at least one of Mn, Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, and M2 includes at least one of Co, Ni, and Mn, 0.5≤x≤1.0, 0≤y<0.5, x+y<1, 0.2≤a<1.2, -0.02≤d<0.02, and 0<z<1.

[0125] Optionally, the layered transition metal oxide includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium-rich material, nickel-cobalt-manganese ternary material and manganese-cobalt-aluminum ternary material.

[0126] The second positive electrode active material has high specific capacity and high voltage platform, and can improve the energy density of the battery.

[0127] It should be noted that the battery will be accompanied by Li deintercalation and consumption during the charging and discharging process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle. In the list of positive electrode materials in this application, the molar content of O is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0128] Among them, Figure 4 The first positive electrode active material layer 32 can be located on the side of the second positive electrode active material layer 33 close to the current collector 31, or can be located on the side of the second positive electrode active material layer 33 close to the current collector 31. Figure 5 The illustrated embodiment is located on the side of the second positive electrode active material layer 33 facing away from the current collector 31 .

[0129] See also Figure 4 According to some embodiments of the present application, the first positive electrode active material layer 32 is located on a side of the second positive electrode active material layer 33 close to the current collector 31 .

[0130] The above configuration can enable the battery to have a better capacity retention rate.

[0131] According to some embodiments of the present application, the present application also provides a battery, comprising a positive electrode plate of any of the above schemes.

[0132] According to some embodiments of the present application, the present application also provides an electrical device, comprising a battery according to any of the above schemes, and the battery is used to provide electrical energy to the electrical device.

[0133] The power-consuming device may be any of the aforementioned devices or systems using batteries.

[0134] According to some embodiments of the present application, see Figure 3 to Figure 4 The present application provides a positive electrode plate 30, which includes a current collector 31, and a first positive electrode active material layer 32 and a second positive electrode active material layer 33 arranged on the current collector 31, the first positive electrode active material layer 32 is located on the side of the second positive electrode active material layer 33 close to the current collector 31, the first positive electrode active material layer 32 includes a first positive electrode active material and a solid lubricant, the first positive electrode active material includes an olivine structure phosphate material, and the electronic conductivity of the first positive electrode active material is 2. The second positive electrode active material layer 33 includes a second positive electrode active material, the second positive electrode active material includes a layered transition metal oxide, and the electronic conductivity of the second positive electrode active material is a2, and a1 is greater than a2.

[0135] Some specific embodiments are listed below to better illustrate the present application.

[0136] Examples and Comparative Examples

[0137]

Preparation of positive electrode

[0138] The preparation of the positive electrode plate in Example 1 includes: preparing a first coating slurry for forming a first positive electrode active material layer: adding carbon-coated LiFePO4, conductive carbon black, MoS2 and PVDF to NMP in a mass ratio of 97.8:0.5:0.4:1.3, and preparing a slurry after stirring.

[0139] A second coating slurry for forming a second positive electrode active material layer was prepared: LiNiCoMnO2, conductive carbon black, and PVDF were added to N-methylpyrrolidone (NMP) at a mass ratio of 98.2:0.5:1.3, and the mixture was stirred to prepare a slurry.

[0140] Preparation of positive electrode sheet: Use extrusion coating to apply the first / second coating slurry in step one to the current collector, dry and cold press to obtain a positive electrode sheet, wherein the first positive electrode active material layer is located on the side of the second positive electrode active material layer close to the current collector.

[0141] Among them, the electronic conductivity of carbon-coated LiFePO4 is 0.5S / cm, and the electronic conductivity of LiNiCoMnO2 is 0.00050S / cm.

[0142] The main parameter controls of Examples 2-9, Comparative Examples 1-2 and Example 1 are shown in Table 1.

[0143] The difference between the preparation method of the positive electrode sheet in Comparative Example 1 and Example 1 is that the carbon-coated LiFePO4 and LiNiCoMnO2 are mixed at a mass ratio of 1:1 as a mixed positive electrode active material, and the mixed positive electrode active material, conductive carbon black, and PVDF are added to NMP at a mass ratio of 98.2:0.5:1.3, and stirred to prepare a slurry. Then, the slurry is applied to the current collector by extrusion coating, dried, and cold pressed to obtain a positive electrode sheet.

[0144] The preparation method of the positive electrode plate in Comparative Example 2 differs from that in Example 1 only in that in the step of preparing the first coating slurry: carbon-coated LiFePO4, conductive carbon black, and PVDF are added to NMP in a mass ratio of 97.8:0.5:1.7 and prepared into a slurry after stirring.

[0145] Table 1 Difference parameters between the embodiment and the comparative example

[0146]

[0147]

Negative electrode sheet preparation

[0148] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are mixed in a weight ratio of graphite: acetylene black: styrene butadiene rubber: sodium carboxymethyl cellulose = 95:2:2:1, and an appropriate amount of deionized water is added and stirred to form a uniform negative electrode slurry; after coating the slurry on the negative electrode current collector copper foil, it is dried and cold pressed to obtain a negative electrode sheet.

[0149]

Isolation film

[0150] Polypropylene film is used as the isolation film.

[0151]

Electrolyte preparation

[0152] The electrolytes were prepared according to the following method: in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were evenly mixed in a volume ratio of 3 / 7, 1 mol / LLiPF6 lithium salt was added and dispersed evenly, and then 2% fluoroethylene carbonate was dissolved in the above organic solvent and stirred evenly to obtain an electrolyte.

[0153]

Battery preparation

[0154] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried battery, and then the battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0155]

Compacted density

[0156] The compaction density of the electrode sheet after rolling is determined according to the following formula: ρ = (M-M0) / (S×H), where M is the mass of the positive electrode sheet to be rolled, M0 is the mass of the current collector, S is the surface area of ​​the current collector, and H is the thickness of the current collector.

[0157]

Battery 25 / 45℃ cycle performance test

[0158] At 25 / 45°C, the batteries prepared in the examples and comparative examples are charged to 4.35V at a constant current of 1C, further charged to a current of 0.05C at a constant voltage of 4.35V, and then discharged to 2V at a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is the initial capacity C1. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time, and detect the discharge capacity of the 200th cycle. The battery capacity retention rate after each cycle is Pn = Cn / C1*100%. After 200 cycles, record C200 and calculate P200 = C200 / C1*100%.

[0159] The results are shown in Table 2.

[0160]

[0161] It can be seen from Table 2 that the positive electrode sheet provided in the present application can improve the compaction density to increase the battery energy density, and can effectively improve the capacity retention rate after cycling.

[0162] According to Examples 1-5, the mass proportion of the solid lubricant in the first positive electrode active material layer not only affects the compaction density of the electrode sheet, but also affects the capacity retention rate after cycling. When the mass proportion of the solid lubricant in the first positive electrode active material layer is 0.1%-6%, the battery has both better energy density and capacity retention rate. When the mass proportion of the solid lubricant in the first positive electrode active material layer is 0.4%-6%, the battery energy density and capacity retention rate are further optimized.

[0163] According to Example 1 and Examples 6-8, it can be known that the relative size of the solid lubricant volume particle size distribution Dv50 and the volume particle size distribution Dv50 of the first positive electrode active material affects the electrode compaction density and capacity retention rate. When the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.3 times the volume particle size distribution Dv50 of the first positive electrode active material, the battery has both better energy density and capacity retention rate. When the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.2 times the volume particle size distribution Dv50 of the first positive electrode active material, the battery energy density and capacity retention rate are further optimized.

[0164] According to Example 1 and Example 9, when the solid lubricant is epoxy resin microspheres or MoS2, the battery energy density and capacity retention rate can be optimized.

[0165] According to Example 1 and Comparative Examples 1-2, since no solid lubricant is added to Comparative Example 1, its pole piece compaction density and capacity retention rate after cycle are significantly worse than those of the embodiment. Compared with Comparative Example 1, Comparative Example 2 adopts layered coating of the first positive electrode material and the second positive electrode material. Compared with the direct physical mixing of the first positive electrode material and the second positive electrode material in Comparative Example 1, although the pole piece compaction density and capacity retention rate after cycle are improved to a certain extent, the effect of the present application is still not achieved.

[0166] Figure 6 This is a SEM image of the phase change at the interlayer interface of the positive electrode sheet provided in Example 1 after 200 cycles. Figure 7 This is a SEM image of the phase change at the interlayer interface of the positive electrode sheet of Comparative Example 2 after 200 cycles. Figure 6 and Figure 7 It can be seen that compared with Comparative Example 2, the thickness of the interface phase change (spinel phase) after cycling in Example 1 is thinner, indicating that the introduction of solid lubricant in the first positive electrode active material layer can reduce the phase change at the interface between the two positive electrode active material layers, so that the battery has a higher cycle capacity retention rate during the cycle process.

[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises a current collector, and a first positive electrode active material layer and a second positive electrode active material layer disposed on the current collector, wherein the first positive electrode active material layer comprises a first positive electrode active material and a solid lubricant, the electronic conductivity of the first positive electrode active material is a1, the second positive electrode active material layer comprises a second positive electrode active material, the electronic conductivity of the second positive electrode active material is a2, and a1 is greater than a2; The electronic conductivity of the solid lubricant is less than a1 and less than or equal to 10 -2 S / cm.

2. The positive electrode sheet according to claim 1, characterized in that: Solid lubricants have a granular or lamellar morphology; Optionally, the particle morphology includes a spherical or quasi-spherical shape.

3. The positive electrode sheet according to claim 1, characterized in that: The volume particle size distribution Dv50 of the solid lubricant is less than or equal to 0.3 times the volume particle size distribution Dv50 of the first positive electrode active material; Optionally, the volume particle size distribution Dv50 of the solid lubricant is 0.05-0.3 times, and optionally 0.05-0.2 times, the volume particle size distribution Dv50 of the first positive electrode active material.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The volume particle size distribution Dv50 of the first positive electrode active material is 0.4-30 um.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The mass proportion of the solid lubricant in the first positive electrode active material layer is less than or equal to 6%, and may be 0.1%-6%, and may further be 0.4%-6%.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The solid lubricant includes at least one of an inorganic lubricant and an organic lubricant; Optionally, the organic lubricant includes thermosetting resin particles, and the thermosetting resin includes at least one of phenolic resin, urea-formaldehyde resin, melamine-formaldehyde resin, epoxy resin, polyurethane resin, and polyimide resin; Optionally, the inorganic lubricant includes at least one of a layered van der Waals material, an inorganic particle having a dielectric constant of 5 or more, and an inorganic particle having ion conductivity but not storing ions; Optionally, the layered van der Waals material comprises molybdenum disulfide; Optionally, the inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1- n Ti n O3、Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 and their respective modified inorganic particles, 0<m<1, 0<n<1; Optionally, the inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following, 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7.

7. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The electronic conductivity of the solid lubricant is 10 -15 -10 -2 S / cm.

8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: 1<a1:a2≤10.

9. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: a1 is 10-10 -9 S / cm; and / or, a2 is 10 -1 -10 -10 S / cm.

10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The first positive electrode active material includes an olivine structure phosphate material, and the second positive electrode active material includes a layered transition metal oxide.

11. The positive electrode sheet according to claim 10, characterized in that: The olivine structure phosphate material includes Li a Fe b M 1-b P 1-m O 4-n , wherein M includes at least one of other metal elements except Fe, wherein 0<a≤1.1, 0.3≤b≤1, 0≤m≤0.1, 0≤n≤0.1; Optionally, M includes at least one of Mn, Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge; Optionally, the olivine structure phosphate material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

12. The positive electrode sheet according to claim 10, characterized in that: The layered transition metal oxides include LiCoO2, LiMnO2, LiNiO2, Li a Ni x Co y M1 1-x-y O 2+d , z Li2MnO3 (1-z) At least one of LiM2O2, wherein M1 includes at least one of Mn, Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, and M2 includes at least one of Co, Ni, and Mn, 0.5≤x≤1.0, 0≤y<0.5, x+y<1, 0.2≤a<1.2, -0.02≤d<0.02, and 0<z<1; Optionally, the layered transition metal oxide includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium-rich material, nickel-cobalt-manganese ternary material and manganese-cobalt-aluminum ternary material.

13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The first positive electrode active material layer is located on a side of the second positive electrode active material layer close to the current collector.

14. A battery, characterized in that: include: A positive electrode sheet as claimed in any one of claims 1 to 13.

15. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 14, wherein the battery is used to provide electrical energy.